Analysis of higher order thinking skills (HOTS) mathematics questions - Fitri Alfarisa; Supriadi Supriadi; Susilawati Susilawati; Annisa Dinur Rahimah; Rizi Suci Litundzira (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study aims to determine the quality of HOTS mathematics questions for fourth grade elementary school students that have been developed. This research is descriptive research with a quantitative approach. The HOTS mathematical instrument was developed with 15 reasoned multiple-choice questions by considering three aspects of HOTS according to Bloom's Taxonomy namely Analyzing (C4), Evaluating (C5), and Creating (C6). The questions were made using fractional material and tested on 15 grade IV students at SD Laboratorium UPI Kampus Serang. The validity of the HOTS instruments was verified by 3 experts in the field of mathematics and continued with calculations using the Aiken V index formula. The quality of the HOTS math questions developed was seen from the validity, reliability, and item difficulty index. The validation results show that all 15 items are valid with an average Aiken index of 0.94. The reliability of the HOTS instrument is also quite reliable with a reliability index of 0.74 which is calculated using Cronbach Alpha. The index of difficulty level of HOTS items is in the range of -1.03 to 1.04. This indicates that all questions are included in HOTS.